Marx en 90 minutos - Strathern, Paul, 1940-; Padilla Villate, José Antonio; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2015)
Strathern briskly outlines the development of Marx's thought as a philosopher and political economist; and as with all titles in this series, illuminates the man behind the ideas.
Online resource; title from ePub title page (Digitalia, viewed June 28, 2017)
Keywords: Marx, Karl, -- 1818-1883.; Communists -- Biography; Communism; Philosophy, Marxist; Electronic books